THE OPTIMIZATION OF MARKETING CHANNELS TO INCREASE BUSINESS INCOME OF LEMON FARMERS IN LEMBANG, INDONESIA - Herlina, Listri; Suryaningprang, Andre; Meltareza, Ridma (Universitas INABA, 2022)
West Bandung Regency, West Java has various types of agricultural products. One of the agricultural products produced is lemon. From the time the pandemic occurred at the end of 2019 until it peaked in 2020 and 2021 demand for lemons increased by 81%. However, at this time in 2022, there is a 50% decrease in demand which has resulted in the income of lemon farmers dropping significantly. One of the causes of the decline in demand is that lemon farmers only focus on a few regular consumers who order large quantities of lemons, as a result, when market demand falls, these consumers will automatically lower their orders. In addition, farmers are unskilled in marketing lemons because they are only used to relying on a few consumers, which makes their garden yields pile up, causing losses. The purpose of this paper is to determine the optimization of effective marketing channels so as to increase the income of lemon farmers.